Violence against women and the substitution of help services in times of lockdown: Triangulation of three data sources in Germany - Cara Ebert; Janina Steinert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
We study the impact of the COVID-19 pandemic on domestic violence against women in Germany in 2020. The analysis draws on three data sources: (1) longitudinal administrative data on the volume of help requests to helplines, shelters and counselling services, (2) cross-sectional survey data collected during the first wave of the pandemic, and (3) a qualitative online survey with counsellors and domestic violence experts. The number of violence-related requests at helplines increased significantly by 29% with the first physical distancing measures, whereas ambulatory care services such as shelters experienced a 19% increase in help requests only after physical distancing restrictions were lifted. Our results indicate that individuals substituted help services away from ambulatory care towards helplines. We do not observe exacerbated violence in states with greater mobility reductions, lower daycare capacity for childcare or higher COVID-19 infection numbers. Our findings highlight the importance of providing easily accessible online counselling offers for survivors of violence and governmental financial relief packages. – – Wir untersuchen die Auswirkungen der COVID-19-Pandemie auf die häusliche Gewalt gegen Frauen in Deutschland im Jahr 2020. Die Analyse stützt sich auf drei Datenquellen: (1) administrative Längsschnittdaten zum Umfang der Hilfeanfragen bei Hotlines, Frauenhäusern und Beratungsdiensten, (2) Querschnittsdaten, die während der ersten Welle der Pandemie erhoben wurden, und (3) eine qualitative Online-Befragung von Fachpersonal für häuslicher Gewalt. Die Zahl der Hilfeanfragen bei Hotlines stieg mit den ersten Socialdistancing-Maßnahmen signifikant um 29 %, während ambulante Dienste wie Notunterkünfte erst nach Aufhebung der Socialdistancing-Maßnahmen einen Anstieg der Hilfeanfragen um 19 % verzeichneten. Unsere Ergebnisse deuten darauf hin, dass Betroffene ambulante Hilfestellen durch Hotlines ersetzt haben. Wir beobachten keinen größeren Zuwachs an Gewalt in Staaten mit größeren Mobilitätseinschränkungen, geringeren Kinderbetreuungskapazitäten oder höheren COVID-19-Infektionszahlen. Unsere Ergebnisse unterstreichen die Bedeutung von leicht zugänglichen Telefon- oder Online-Hilfsangeboten und von finanziellen Entlastungsangeboten der Regierung.
Keywords: J12; J16; J18; I18; 330; COVID-19; lockdown; violence against women; event study